Cruise Tourism and Sea Ice in Canada's Hudson Bay Region - Stewart, E.J.; Tivy, A.; Howell, S.E.L.; Dawson, J.; Draper, D. (ARCTIC, 2010)
Tourism in the Hudson Bay region of central northern Canada generally is associated with non-consumptive forms of nature-based activities (such as polar bear viewing). However, the region has experienced variable growth in the cruise sector in recent years. This paper examines patterns of cruise activity in all subregions of the Hudson Bay region during three cruise seasons (2006, 2008, and 2009) and mainly reveals a pattern of decline. Since the prevalence of sea ice is an important part of visitor experiences of polar cruises, we examine sea ice change and occurrence of icebergs in the Hudson Bay region. Our sea ice analysis suggests that the length of the navigable shipping season is increasing in this region, which may facilitate both earlier and later shipping. But in terms of cruise traffic, we suggest that the demise of ice coverage signals a possible decline in cruise activity in most of the Hudson Bay region because ice-supported wildlife may shift north with the diminishing ice regime. Given the possible environmental and socio-cultural implications of changing cruise activity patterns in the Arctic and the absence of broad-scale monitoring and surveillance of the industry, use of these available data sources is vital to building a clearer picture. De manière générale, le tourisme dans la région de la baie d’Hudson du centre-nord du Canada se rapporte à des activités non consomptibles en plein air (comme l’observation des ours polaires). Toutefois, ces dernières années, le secteur des croisières de cette région a enregistré un taux de croissance variable. La présente communication se penche sur les tendances en matière de croisières dans toutes les sous-régions de la région de la baie d’Hudson au cours de trois saisons de croisière (2006, 2008 et 2009), ce qui laisse principalement entrevoir un déclin à cet égard. Puisque l’existence de glace de mer revêt une grande importance pour les visiteurs des croisières polaires, nous avons examiné les changements en matière de glace de mer et l’occurrence ...